(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article explores the scientific and practical foundations of organizing the educational process in pedagogical higher education institutions based on individual learning technologies. It analyzes the mechanisms of forming students’ individual learning trajectories, including self-awareness, self-assessment, design, forecasting of development points, and the application of newly acquired knowledge in practice. The study highlights the concepts of Individual Learning Content (ILC), Individual Learning Levels (ILL), and Individual Learning Trajectory (ILT), emphasizing their integration as a key factor in enhancing the effectiveness of modern education. The research findings propose recommendations for developing students’ personalized learning pathways, implementing reflective evaluation, and improving the overall quality of education.